On (?m, I)-Statistical Convergence of Order ? - Et, Mikail; Alotaibi, Abdullah; Mohiuddine, S. A. (Hindawi Ltd, 2014)
The idea of I-convergence of real sequences was introduced by Kostyrko et al., (2000/01) and also independently by Nuray and Ruckle (2000). In this paper, we introduce the concepts of (Delta(m), I)-statistical convergence of order alpha and strong (Delta(m)(p), I)-Cesaro summability of order alpha of real sequences and investigated their relationship.
Keywords: Generalized Difference-Sequences; Statistical Convergence; Approximation Theorems; Ideal Convergence; Spaces; Lambda